2021
DOI: 10.1186/s43093-021-00089-2
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of African trade blocs effects on the global economy: new evidence from the gravity model

Abstract: This study employs the gravity model to estimate the extent of the contribution of six African trade blocs to the global economy using the gravity model spanning from 1980 to 2018. The gravity equation that models the export contributions of the six selected African RECs to the global export is estimated. The estimated gravity model reveals that the long run estimations show that the coefficient estimate for SACU and ECCAS are insignificant in the long run while SACU, EAC and ECCAS as RECs, have insignificant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, a study conducted by Riyani Rifin [102] shows that in Malaysia, the decline in the value of exports may be caused by several obstacles, such as import duties and tariff and non-tariff policies. The significance of the relationship between treaty institutions and trade is reflected in research that confirms how weak treaty institutions can restrict international trade with negative effects [103,104]. In addition, poor institutional quality can hinder trade and lead to poor export performance [105].…”
Section: Discussionmentioning
confidence: 96%
“…However, a study conducted by Riyani Rifin [102] shows that in Malaysia, the decline in the value of exports may be caused by several obstacles, such as import duties and tariff and non-tariff policies. The significance of the relationship between treaty institutions and trade is reflected in research that confirms how weak treaty institutions can restrict international trade with negative effects [103,104]. In addition, poor institutional quality can hinder trade and lead to poor export performance [105].…”
Section: Discussionmentioning
confidence: 96%
“…The problem with Fadeyi et al (2014) study is that it was done just a year after the full implementation of the SADC FTA and its possible that the effects had not fully permeated into the economies. The mixed results found by studies by Afesorgbor (2017), Afesorgbor (2019), Olayungbo and Iqbal (2021) and Admassu (2019) on regional integration effects show that there is no consensus and results probably depend on data timelines used and data analysis techniques followed etc.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In the case of Africa, most of the studies focus mainly on analysing the impact of regional trade agreements (RTAs) on trade growth finding mixed results. Admassu (2019), using a comprehensive dataset of 148 countries for the period 1970–2010, found robust evidence that African RECs increase their members’ exports and imports, albeit with varying degrees whilst Olayungbo and Iqbal (2021) found that Common Market for East and Southern Africa (COMESA) has the highest contribution to the global exports, followed by East African Community (EAC), Economic Community for West African States (ECOWAS) and SADC with Economic Community of Central African States (ECCAS) and Southern African Customs Union (SACU) the lowest contributors. The positive effect of EAC on trade is confirmed by Umulisa (2020) and Buigut (2016) with the later finding that the EAC customs union produced a moderate positive effect on intra-EAC trade of about 22.1%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firms that have managed to integrate into value chains experience growth, technological upgrading, and maintain stability [1][2][3][4]. Regional arrangements such as those of regional blocs such as the East African Community (EAC) offer potential for organized production networks that span multiple countries and enable inter-firm governance structures that shape productive economies and drive international trade at global and regional levels [5][6][7]. Regional value chains (RVCs) represent cross-border organized value chain activities in the same region (at the regional level), for example within the East African Community (EAC) or in Africa as a region.…”
Section: Introductionmentioning
confidence: 99%
“…One of the proposed ways to increase the domestic value added of exports in low-income countries is to create an environment that attracts both domestic and foreign direct investment (FDI). Several previous studies have shown that the specific conditions of the host country and the existence of regional integration programs can play an important role in attracting investments worldwide [7,[18][19][20]. In particular, foreign direct investment plays a crucial role in the industrialization process by facilitating access to capital, technology and new managerial skills, and enabling the integration of local economies with international markets through export trade [21][22][23].…”
Section: Introductionmentioning
confidence: 99%